Paraneoplastic neurological complications of breast cancer. Issue 1 (December 2015) - Fanous, Ibrahim; Dillon, Patrick
Abstract Breast cancer is the most frequent cause of cancer of women in much of the world. In countries with screening programs, breast cancer is often detected before clinical symptoms are apparent, but occasionally the occurrence of a paraneoplastic syndrome precedes the identification of cancer. In breast cancer, there are known to be paraneoplastic endocrine syndromes and neurologic syndromes. The neurologic syndromes are often hard to identify and treat. The neurologic syndromes associated with breast cancer include cerebellar degeneration, sensorimotor neuropathy, retinopathy, stiff-persons syndrome, encephalitis, and opsoclonus–myoclonus. Most of these are mediated by antibodies against known neural antigens, although some cases appear to be mediated by non-humoral mechanisms. Treatments differ depending upon the syndrome type and etiology. Outcomes also vary depending upon duration of disease, the treatments used and the responsiveness of the underlying cancer. A thorough review of the published literature is provided along with recommendations for management and future research.